2019
DOI: 10.1111/dme.14042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of comorbid major depressive disorder in Type 2 diabetes: a meta‐analysis of comparative and epidemiological studies

Abstract: Aims To examine the average point prevalence of major depressive disorder in people with Type 2 diabetes and its associated factors in a comprehensive meta‐analysis. Methods Two researchers independently conducted a systematic literature search of PubMed, EMBASE, PsycINFO and Cochrane databases. Studies reporting the prevalence of major depressive disorder in people with Type 2 diabetes were identified and analysed using a random‐effects model. Results A total of 26 studies meeting the inclusion criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 62 publications
1
52
0
5
Order By: Relevance
“…We further constrained prevalence estimates to validated depression questionnaires that reported prevalence based on questionnaire cut‐offs, excluding studies that used clinical interviewing, which represents a more comprehensive and recommended method of assessing depression. However, a recent meta‐analysis of 26 studies that used ICD or DSM diagnostic interviewing to diagnose depression in Type 2 diabetes revealed broadly the same pattern of results as reported above. Depression prevalence was higher in Type 2 diabetes than in controls (at 14.5% in all studies, and 9.2% vs. 4.3% in 10 case–control studies comparing Type 2 diabetes and general population samples).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We further constrained prevalence estimates to validated depression questionnaires that reported prevalence based on questionnaire cut‐offs, excluding studies that used clinical interviewing, which represents a more comprehensive and recommended method of assessing depression. However, a recent meta‐analysis of 26 studies that used ICD or DSM diagnostic interviewing to diagnose depression in Type 2 diabetes revealed broadly the same pattern of results as reported above. Depression prevalence was higher in Type 2 diabetes than in controls (at 14.5% in all studies, and 9.2% vs. 4.3% in 10 case–control studies comparing Type 2 diabetes and general population samples).…”
Section: Discussionsupporting
confidence: 62%
“…That said, many settings lack funding to support skilled diagnostic interviewing, as reflected by the small number of studies eligible for inclusion in Wang et al . compared with the 147 studies we were able to analyse. As such, questionnaire measures still form an important element of the evaluation of people with Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the sample size equation n = Z 2 α/2 P(1-P)/δ 2 (Zhou et al, 2012), type I error (α) was set at 0.05, and Z α/2 was set at 1.96. For prevalence (P), we used a reference value of 14.5%, consistent with a previous study that estimated the prevalence of depressive disorder in patients with T2DM (Wang et al, 2019). We used 0.03 for the absolute error (δ).…”
Section: Setting and Samplementioning
confidence: 99%
“…Results of several developing countries' epidemiological studies showed the prevalence of depression in T2DM ranged from 34% to 54% [19][20][21] . 28% T2DM patients have depression at different degrees [22] , and 14.5% have major depressive disorder [23] . In China, relevant epidemiological investigations have also been carried out in quantity.…”
Section: Introductionmentioning
confidence: 99%